Capacity Building sebagai Strategi dalam Upaya Peningkatan Kualitas Pelayanan Kebencanaan di Kabupaten Jombang - Nieke Rudyanty winanda; Muhammad Nur Hidayat; Risdianto Adi Firdaus (Universitas Medan Area, 2026)
Disasters have widespread impacts on society, thereby requiring an active role for government in delivering public services in the disaster management sector. This study aims to analyze the implementation of capacity building as an alternative strategy to improve the quality of disaster management services in Jombang Regency. This research employs a qualitative, descriptive design. Data sources consist of primary and secondary data, collected through interviews, observations, and documentation. The informants include officials and personnel from the Regional Disaster Management Agency (BPBD) and Fire and Rescue Services (Damkar) of Jombang Regency. Data analysis uses the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that efforts to improve disaster management services have been implemented through various programs, including disaster education and personnel training. However, the implementation of capacity building, which includes human resource development, organizational strengthening, and institutional reform, has not been fully optimized. The main challenges include limited budget, inadequate infrastructure, and the institutional integration of BPBD and Damkar, which affects organizational effectiveness. This study highlights that capacity building functions not only as a means of enhancing individual capacity but also as a strategy for institutional reform in disaster governance. Therefore, stronger policy support and commitment from local government are needed to optimize capacity-building implementation and achieve more responsive, effective, and community-oriented disaster management services.